Survival outcomes of appendiceal mucinous neoplasms by histological type and stage: Analysis of 266 cases in a multicenter collaborative retrospective clinical study. Issue 3 (25th February 2019) - Sueda, Toshinori; Murata, Kohei; Takeda, Takashi; Kagawa, Yoshinori; Hasegawa, Junichi; Komori, Takamichi; Noura, Shingo; Ikeda, Kimimasa; Tsujie, Masaki; Ohue, Masayuki; Ota, Hirofumi; Ikenaga, Masakazu; et al.
Abstract: Aim: Appendiceal mucinous neoplasms are rare, and thus the literature is sparse with regard to histological types, staging, and prognosis. In particular, it is unclear how long‐term outcome may differ between mucinous adenocarcinomas and other adenocarcinomas. In the present study, we aimed to investigate the histological types and stages of appendiceal neoplasms, and to evaluate the prognostic impacts of these factors in patients with mucinous adenocarcinomas and non‐mucinous adenocarcinomas. Methods: Patients with appendiceal tumors diagnosed between 2007 and 2016 were retrospectively identified from the databases of 19 institutions in the Clinical Study Group of Osaka University, Colorectal Group. Results: A total of 266 patients with appendiceal tumors were identified, of whom 130 had pathologically diagnosed adenocarcinomas, including 57 with mucinous adenocarcinomas and 73 with non‐mucinous adenocarcinomas. Five‐year overall survival (OS) rates were 64.5% for mucinous adenocarcinomas, and 49.0% for non‐mucinous adenocarcinomas. OS was significantly shorter among patients with non‐mucinous adenocarcinomas compared to mucinous adenocarcinomas. Among patients with mucinous adenocarcinomas, 5‐year OS rates were 53.6% for stage 0/I, 82.6% for II/III, and 48.4% for IV. Among patients with non‐mucinous adenocarcinomas, 5‐year OS rates were 90.9% for stage 0/I, 68.8% for II/III, and 7.1% for IV. Analysis of patients with stage IV disease revealed significantly shorter OS among patients with non‐mucinous adenocarcinomas compared to mucinous adenocarcinomas. Conclusion: Our present findings showed a better prognosis in patients with mucinous adenocarcinomas compared to non‐mucinous adenocarcinomas. In this setting, Union for International Cancer Control staging was associated with prognosis for non‐mucinous adenocarcinomas, but not for mucinous adenocarcinomas. Abstract : Appendiceal mucinous adenocarcinomas are associated with better prognosis than non‐mucinous adenocarcinomas.